2021
DOI: 10.1002/hep.31992
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Stereotactic Body Radiation Therapy for Hepatocellular Carcinoma on Waitlist for Liver Transplant

Abstract: BaCKgRoUND aND aIMS:There are no prospective data on stereotactic body radiation therapy (SBRT) as a bridge to liver transplantation for HCC. This study aimed to evaluate the efficacy and safety of SBRT as bridging therapy, with comparison with transarterial chemoembolization (TACE) and high-intensity focused ultrasound (HIFU).appRoaCH aND ReSUltS: Patients were prospectively enrolled for SBRT under a standardized protocol from July 2015 and compared with a retrospective cohort of patients who underwent TACE o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 43 publications
(86 reference statements)
3
32
0
2
Order By: Relevance
“…SBRT was demonstrated to be safe, with a significantly higher tumor control rate and reduced risk of waitlist dropout. The Authors concluded that SBRT should be used as an alternative to conventional bridging therapies [ 88 ].…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…SBRT was demonstrated to be safe, with a significantly higher tumor control rate and reduced risk of waitlist dropout. The Authors concluded that SBRT should be used as an alternative to conventional bridging therapies [ 88 ].…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…The frequency of complete pathological necrosis of the tumor after SBRT varies from 13.3% to 61.5% [ 101 , 117 , 118 ]. Wong et al [ 119 ] reported that pre-transplant SBRT had a higher frequency of complete pathological necrosis and a lower frequency of drop-outs from the waiting list compared to conventional bridging therapy.…”
Section: Variations Of Pre-transplant Locoregional Therapiesmentioning
confidence: 99%
“…We appreciate the interests and comments by Sahai et al The median dose of stereotactic body radiation therapy (SBRT) of our patients was 50 Gy (range 30–50 Gy). [ 1 ] In addition, the maximum dose of planning target volume was usually set at 130% of the prescribed dose, which ranged from 108% to 130% of the prescribed dose in our study.…”
mentioning
confidence: 99%